2013
DOI: 10.4323/rjlm.2013.111
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cocaine and its major metabolite benzoylecgonine in rabbit hair by GC/MS

Abstract: It is important to determine people who use drugs to prevent the use of them. In recent years, hair is routinely used on toxicological analysis as well as biological samples such as blood and urine. The major practical advantages of hair testing are larger detection windows; non-invasive sample collection; easy to transport and store in addition hair analysis can provide a retrospective calendar of an individual's drug use history. In this study, Male New Zealand rabbits (n=10) weighing 2-2,5 kg were used. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Benzoylecgonine is the main metabolite of cocaine and an analgesic from the pharmaceutical industry (Efeoglu et al, 2013). Several studies have been reported the existence of Benzoylecgonine in different water bodies, around the globe.…”
Section: Benzoylecgoninementioning
confidence: 99%
“…Benzoylecgonine is the main metabolite of cocaine and an analgesic from the pharmaceutical industry (Efeoglu et al, 2013). Several studies have been reported the existence of Benzoylecgonine in different water bodies, around the globe.…”
Section: Benzoylecgoninementioning
confidence: 99%